2018
DOI: 10.1016/j.carbpol.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanofibers from banana peels as a Pickering emulsifier: High-energy emulsification processes

Abstract: Cellulose nanofibers (CNFs) from banana peels was evaluated as promising stabilizer for oil-in-water emulsions. CNFs were treated using ultrasound and high-pressure homogenizer. Changes on the size, crystallinity index and zeta potential of CNFs were associated with the intense effects of cavitation phenomenon and shear forces promoted by mechanical treatments. CNFs-stabilized emulsions were produced under the same process conditions as the particles. Coalescence phenomenon was observed in the emulsions produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(57 citation statements)
references
References 48 publications
1
56
0
Order By: Relevance
“…For instance, the higher quantity of ash can be valuable in treating deficiencies of minerals caused by celiac disease (Presutti et al 2007). Additionally, several studies have shown the application of BPe as a low-cost precursor for producing materials such as anionic dye and heavy metal adsorbents (Mahindrakar and Rathod 2018;Munagapati et al 2018;Oyewo et al 2018;Singh et al 2018;Vilardi et al 2018), recovering phenolic compounds (Vu et al 2018), producing cellulose nanofibers (Costa et al 2018;Harini et al 2018;Tibolla et al 2018), as well as bioethanol (Berawi and Bimandama 2018;Prakash et al 2018) and pectin extract (Khamsucharit et al 2018). In the following sections, some of the exclusive added value components in banana are introduced.…”
Section: Composition Of Bananamentioning
confidence: 99%
“…For instance, the higher quantity of ash can be valuable in treating deficiencies of minerals caused by celiac disease (Presutti et al 2007). Additionally, several studies have shown the application of BPe as a low-cost precursor for producing materials such as anionic dye and heavy metal adsorbents (Mahindrakar and Rathod 2018;Munagapati et al 2018;Oyewo et al 2018;Singh et al 2018;Vilardi et al 2018), recovering phenolic compounds (Vu et al 2018), producing cellulose nanofibers (Costa et al 2018;Harini et al 2018;Tibolla et al 2018), as well as bioethanol (Berawi and Bimandama 2018;Prakash et al 2018) and pectin extract (Khamsucharit et al 2018). In the following sections, some of the exclusive added value components in banana are introduced.…”
Section: Composition Of Bananamentioning
confidence: 99%
“…While it is not always mentioned nor discussed, the recent literature shows that depletion flocculation is prevalent in emulsion stabilized by primary plant cell materials. To name a few examples, CMF extracted from mangosteen rinds,18,43 orange pulp20 and banana peels44 yield emulsions with similar droplet sizes to our system, and droplets are also flocculated even at low CMF concentrations. This is likely due to the presence of soluble polymers from the plant cell wall material the CMF were extracted from: despite their very low concentration in the plant dispersion, they have a considerable influence on the resulting microstructure of the emulsions.…”
mentioning
confidence: 72%
“…Enzymatic hydrolysis is another green method and less energy consuming used to generate CNFs or CNCs. The main enzymes used are cellulases, as endoglucanase and β-glucosidase, and xylanase [ 45 , 63 , 64 ]. For example, Costa et al [ 45 ] used xylanase to produce CNFs from banana peels.…”
Section: Eco-friendly Pickering Emulsionsmentioning
confidence: 99%
“…The main enzymes used are cellulases, as endoglucanase and β-glucosidase, and xylanase [ 45 , 63 , 64 ]. For example, Costa et al [ 45 ] used xylanase to produce CNFs from banana peels. Xylanase hydrolyzed all hemicelluloses and initiated hydrolysis of β(1-4) glycosidic bonds of cellulose amorphous regions.…”
Section: Eco-friendly Pickering Emulsionsmentioning
confidence: 99%
See 1 more Smart Citation